Electronic-cigarette use among young people in Wales: evidence from two cross-sectional surveys. Issue 4 (15th April 2015) - Moore, Graham; Hewitt, Gillian; Evans, John; Littlecott, Hannah J; Holliday, Jo; Ahmed, Nilufar; Moore, Laurence; Murphy, Simon; Fletcher, Adam
Abstract : Objectives: To examine the prevalence of electronic(e)-cigarette use, prevalence of e-cigarette and tobacco use by age, and associations of e-cigarette use with sociodemographic characteristics, tobacco and cannabis use among young people in Wales. Design: Data from two nationally-representative cross-sectional surveys undertaken in 2013–2014. Logistic regression analyses, adjusting for school-level clustering, examined sociodemographic characteristics of e-cigarette use, and associations between e-cigarette use and smoking. Setting: Primary and secondary schools in Wales. Participants: Primary-school children aged 10–11 (n=1601) and secondary-school students aged 11–16 (n=9055). Results: Primary-school children were more likely to have used e-cigarettes (5.8%) than tobacco (1.6%). Ever use of e-cigarettes remained more prevalent than ever use of tobacco until age 14–15. Overall, 12.3% of secondary-school students (aged 11–16) reported ever using e-cigarettes, with no differences according to gender, ethnicity or family affluence. The percentage of 'never smokers' reporting having used e-cigarettes was 5.3% at age 10–11 to 8.0% at age 15–16. The proportion of children who had ever used an e-cigarette and reported currently smoking increased from 6.9% among 10–11 year olds to 39.2% in 15–16 year olds. Only 1.5% (n=125) of 11–16 year-olds, including 0.3% of never smokers, reported regular e-cigarette use (use at least once a month). Current weekly smokers were 100 times more likely than non-smokers to report regular e-cigarette use (relative risk ratio (RRR=121.15; 95% CI 57.56 to 254.97). Regular e-cigarette use was also more likely among those who had smoked cannabis (RRR 53.03; 95% CI 38.87 to 80.65). Conclusions: Many young people (including never-smokers) have tried e-cigarettes. However, regular use is less common, and is associated with tobacco cigarette use. Longitudinal research is needed to understand age-related trajectories of e-cigarette use and to understand the temporal nature of relationships between e-cigarette and tobacco use.